A practical guidance on the use of intravenous insulin infusion for management of inpatient hyperglycemia: Intravenous Insulin Infusion for Management of Inpatient Hyperglycemia. Issue 5 (September 2021) - Goyal, Alpesh; Mathew, Uthara Elsa; Golla, Kiran Kumar; Mannar, Velmurugan; Kubihal, Suraj; Gupta, Yashdeep; Tandon, Nikhil
Abstract: Background: We aim to provide a practical guidance on the use of intravenous insulin infusion for managing inpatient hyperglycemia. Methods and results: This document was formulated based on the review of available literature and personal experience of authors. We have used various case scenarios to illustrate variables which should be taken into account when deciding adjustments in infusion rate, including but not restricted to ambient blood glucose level and magnitude of blood glucose change in the previous hour. Conclusion: The guidance can be generalized to any situation where dedicated protocols are lacking, trained manpower is not available and resource constraints are present. Highlights: Insulin is the most rapid and effective therapy for achieving glycemic control in hospitalised patients. This review provides a practical guide on the use of intravenous insulin for managing inpatient hyperglycemia. The guidance can be generalized to situations where dedicated protocols are lacking, and trained manpower is not available.